Competency-Based Education Reform in Developing Countries: A Systematic and Critical Review - Mansouri, Youssef El; Benhaddou, Fatima Zahra; Lahcen, Rachid Aït (SCIENTIA: Journal of Multi Disciplinary Science, 2025)
This study provides a comprehensive systematic and critical review of the competency-based education (CBE) reform movement across developing countries. Over the past two decades, CBE has emerged as a global paradigm shift emphasizing learning outcomes, skill mastery, and lifelong adaptability. Yet, despite its conceptual appeal, the translation of CBE into effective educational practice in developing contexts remains highly uneven. Drawing upon 112 peer-reviewed journal articles and policy documents published between 2000 and 2025, this review explores three major themes: (1) the philosophical and policy foundations of CBE reform; (2) the implementation challenges faced by education systems with limited institutional capacity; and (3) the pedagogical and assessment innovations required for competency-based learning to succeed. Findings reveal that while CBE reform has stimulated discourse on educational quality, equity, and employability, its enactment often suffers from misalignment between curriculum design, teacher training, and evaluation systems. The paper concludes by proposing a multidimensional framework for rethinking CBE reform that integrates local knowledge, cultural contextualization, and systemic governance approaches. This review contributes to global educational reform scholarship by highlighting the dialectic tension between global policy transfer and contextual adaptation in developing world settings.